Roman life - Guy, John.; Barron's Educational Series, inc. (Hauppauge, N.Y. : Barron's, 1998)
Text and illustrations cover ancient Roman society, culture, art, religion, warfare, and institutions.
"First published in Great Britain in 1998 by ticktock Publishing Ltd.".
Includes index.
Young Adult
Keywords: City and town life -- Italy -- Rome -- History; Rome (Italy) -- Social life and customs; Rome -- History -- Juvenile literature; Rome -- Social life and customs -- Juvenile literature; Rome -- History; Rome -- Social life and customs; Rome -- History; Rome -- Social life and customs